2013
DOI: 10.1007/s10508-013-0205-y
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating Couples-Based Approaches into HIV Prevention for Gay and Bisexual Men: Opportunities and Challenges

Abstract: Thirty years after the beginning of the HIV epidemic, gay, bisexual, and other men who have sex with men (collectively called MSM) bear a disproportionate burden of HIV in the United States and continue to acquire a distressingly high number and proportion of new infections. Historically, HIV prevention for MSM has been focused on individual-level behavior change, rarely intervening with MSM as part of a couple. Yet, an estimated 33–67% of HIV infections among MSM are acquired from primary sexual partners, sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 82 publications
1
28
0
Order By: Relevance
“…New research shows that sexual negotiations begin early in the relationship, before couples discuss their agreements about whether to allow sex with outside partners and that having an agreement is associated with testing (Mitchell, in press; Mitchell & Petroll, 2012a). Messages, announcements, and campaigns that emphasize testing could encourage men to do so when forming their sexual agreements (i.e., whether to allow sex with outside partners) early in their relationships as this may be a time when HIV risk is elevated and they are motivated (Davidovich, et al, 2004; Purcell, et al, 2014; Rendina, et al, 2014). These efforts need not end where relationships begin, as there are opportunities to emphasize HIV testing for partners in couples throughout the course of the relationship.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…New research shows that sexual negotiations begin early in the relationship, before couples discuss their agreements about whether to allow sex with outside partners and that having an agreement is associated with testing (Mitchell, in press; Mitchell & Petroll, 2012a). Messages, announcements, and campaigns that emphasize testing could encourage men to do so when forming their sexual agreements (i.e., whether to allow sex with outside partners) early in their relationships as this may be a time when HIV risk is elevated and they are motivated (Davidovich, et al, 2004; Purcell, et al, 2014; Rendina, et al, 2014). These efforts need not end where relationships begin, as there are opportunities to emphasize HIV testing for partners in couples throughout the course of the relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that men in relationships endorse CHTC and that CHTC supports the relationship (Stephenson, et al, 2011; Wagenaar, et al, 2012). Gay men’s testing during relationship formation to establish trust and commitment could dovetail with efforts that promote HIV testing for gay men in relationships (Purcell, et al, 2014). Home testing for HIV has been shown to be popular among and empowering to gay men and to increase HIV testing (Carballo-Diéguez, Frasca, Balan, Ibitoye, & Dolezal, 2012; Carballo-Diéguez, Frasca, Dolezal, & Balan, 2012; MacKellar, et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It is estimated that 33-67% of HIV infections in MSM are acquired from primary sexual partners (204) and in the UK approximately 40% of MSM are in a regular relationship at the time of diagnosis (7). A high proportion of young MSM interviewed in Scotland aspired to sex within relationships (205) and proofreading changes included in published version which is available on the BASHH website.…”
Section: Motivation For and Barriers To Hiv Testingmentioning
confidence: 99%
“…HIV research among GBM has identified the importance of focusing on same-sex male dyads, recognizing that it is important to understand not only individual-level decision-making, but decisions about relationships and sex that occur between partners (Mustanski & Parsons, 2014;Purcell et al, 2014). The influence of one'spartner's identity on perceptions and the inferences made about risk based on perceptions of a population's risk level add an additional layer to the understanding of how an individual's gay identity, or their perception of other's identities, influences their willingness to participate in sexual risk-taking.…”
Section: Discussionmentioning
confidence: 99%